Assessment of financial management of the National Health Fund in 2005-2011 - Gastecka, Agata (Progress in Economic Sciences; No 2 (2015): Progress in Economic SciencesDO - 10.14595/PES/02/003, 2015)
After many reforms of the Polish health care system, the current entity responsible for financing medical services to the insured patients is the National Health Fund. Despite the constantly increasing funds being allocated to the health care system, it still remains underfunded. A tool that facilitates the evaluation and assessment of the viability, stability and profitability of a business is called the financial analysis. The primary source of data necessary for the preparation of the financial analysis comes from the financial statement which includes the balance sheets, profit and loss account, notes, cash flow statement, and statement of changes in equity. On the basis of the information contained in these documents one can understand the structure of assets, earnings, revenues and expenses, as well as the level of indebtedness and liquidity. The National Health Fund has a monopoly on the health insurance market. Therefore, the financial management conducted by this entity should be based on the rationalization of the expenditure in terms of revenue and stable income generation. The financial analysis carried out between 2005 and 2011 showed that the total assets of the entity were dominated by the current assets which can be justified by the nature of the business. The structure of equity relative compared to the foreign capital did not show positive trends. Since 2009, the bad financial situation was manifested by the profit and loss accounts, which reached negative values and costs exceeding the revenue. The ratio analysis showed a high debt rates experienced by the health care payers. At the same time, however, the liquidity has been maintained.